The Performance of Plasmonic Gold and Silver Nanoparticle-Based SERS Sensors - Alwan, Alwan M.; Mohammed, Mohammed S.; Shehab, Russul M. (Iraqi Journal of Science, 2020)
The influence of different types of plasmonic gold (Au-NPs) and silver (Ag-NPs) nanoparticles as well as aging on the performance of Surface-Enhanced Raman Scattering (SERS) sensors were studied. The average diameters of Au-NPs and Ag-NPs were about 23 nm and 15 nm, respectively, with a number of laser pulses of about 200. plasmonic nanoparticles were synthesized by laser ablation process in distilled water using a fixed energy laser fluence of about 14 J/cm2 of Nd-YAG laser, with 1060 nm wavelength and 1 Hz pulse repetition rate. The SERS sensor was carried out by quick drop casting process of plasmonicplasmonic nanoparticles on glass substrates. The morphological aspects and the performance of SERS sensors were investigated by high resolution transmission electron microscopy (HR-TEM) and Raman spectroscopy. All the results indicated the significant dependence of the performance of the sensor on the types of the plasmonic nanoparticles . The obtained Raman signal intensity of Ag-NPs was about 105a.u. compared with 103a.u. for Au-NPs. While, the stability of Au-NPs was much higher than that of Ag-NPs based on SERS sensors due to the normal oxidation process of Ag-NPs.